PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS (Studi Empiris pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2015) - Vina Afidatul Maula; Dul Mu'id (Diponegoro Journal of Accounting, 2017)
This research is intended to analyze the influence of working capital management, earnings management, working capital management theory, company size, leverage to profitability of manufacturing company which goods in Indonesia Stock Exchange period 2014 until 2015. The sample in this study is a manufacturing company that goods on the Indonesia Stock Exchange period 2014 to 2015. Data data by method. Method and test of determination (R2). To analyze the data using multiple regression.